Effect. Strategy. Concepts. Cartoon. In Achievement. Science. on female students. Fifth grade. Elementary school. (Journal of the College of Basic Education, 2022)
The.current.research.aims.to.identify.the.impact.of the.strategy.of.the .concepts.of.the .cardiology. in the.achievement.of.science.in.the.students.of thee fifth. grade. primary. In.order.to.achieve.the.research.objective.,the .following.research.hypothesis.was.formulated: (There.is.no.statistically. significant.difference.at.the.level.of (.0.05.) between.the.average achievement.of students.who.studied.science.with.the.strategy.of.the concepts.of.cardboard.and the.average achievement.of students.who studied science.in.the traditional.way). As.for the research.community, the.researcher.deliberately.chose.Shaimaa Primary.School. The.total.sample.was (62.), such.as 31.student .of.the experimental.group., and.31.students.of the.control group.. The.researcher.conducted the.equivalence.between the.two groups.of research.in.the following.variables: grades.of.students.in the fourth.grade in science, .and in.the level.of intelligence.,and the.statistica.ltreatment.showed that.there.are.no.significant.differences between.the two.groups of.research, which.means.that they.are equal.in.these.variables.The.researcher.prepared the.teaching.plans.fo.rthe.subjects.of the.study.of.the two.groups and.was presented.to a group.of arbitrators.. The.researcher prepared.the objectives.for.the special.behavior.of the.study content..The.statistical methods.used in.the.analysis.of research.data.are:1-T - test.to.find.out.the.significance of.differences between.the two.search groups.in.equivalence.Pearson.correlation.coefficient2-Equating.the difficulty.of the.paragraph.and.distinguish.them.The.research.found the following.result: The.students.of.the.experimental group.who.studied.science.with.the.strategy.of the.Carton concepts.emerged as.the.students of the.control group.who studied.science in the.traditional way.>>In.light.of .the.results, the.researcher.presented a number.of conclusions., recommendations.and.suggestions:The.importance.of using. the.strategy.of the.concepts.of cardiology.in.the curricula.of the.faculties.of basic.education and.faculties. The.importance of using.the.strategy of the.concepts of.cardiology in the.teaching of.science.for the.fifth grade.of primary.because of thei. positive.effect.in the.achievement of.the.students.helps to.raise.the students'.achievement.and .their.level.of awareness. .Education.to.understand these.strategies.and how to.use them, holding.courses, seminars.and lectures.to.clarify.the recent.strategies.close to the.same.child for.teachers.and educationa.lsupervisors, not.to.acquire.the necessary.skill , The.preparation.of a booklet.from the.Ministry.of.Education, including.modern.teaching.methods, including.the strategy.of concepts.that can.be.used in the.teaching of.science, and.distributed to.schools to.be accessible.to science.teachers..